Efficient datamining model for prediction of chronic kidney disease using wrapper methods - Ramaswamyreddy A; Shiva Prasad S; K V Rangarao; A Saranya (Institute of Advanced Engineering and Science, 2019)
In the present generation, majority of the people are highly affected by kidney diseases. Among them, chronic kidney is the most common life threatening disease which can be prevented by early detection. Histological grade in chronic kidney disease provides clinically important prognostic information. Therefore, machine learning techniques are applied on the information collected from previously diagnosed patients in order to discover the knowledge and patterns for making precise predictions. A large number of features exist in the raw data in which some may cause low information and error; hence feature selection techniques can be used to retrieve useful subset of features and to improve the computation performance. In this manuscript we use a set of Filter, Wrapper methods followed by Bagging and Boosting models with parameter tuning technique to classify chronic kidney disease. The capability of Bagging and Boosting classifiers are compared and the best ensemble classifier which attains high stability with better promising results is identified.